2008
DOI: 10.1158/1055-9965.epi-08-0086
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent for Biorepositories: Assessing Prospective Participants' Understanding and Opinions

Abstract: Purpose: Obtaining informed consent for the collection, storage, and future research use of biospecimens is challenging, as potentially complex and controversial information must be communicated clearly. We gathered input on a consent template developed for the Duke Biorepository from individuals representative of those who might one day consider contributing specimens. Methods: Forty subjects were recruited from the Durham, NC area and screened to achieve diversity by race/ethnicity, education, age, and sex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 26 publications
5
100
1
Order By: Relevance
“…i.e, limiting to oneself and not disclosing to others. [10][11][12][13][14] These findings were in agreement with the study done by Kaufman DJ 2009 and Hansson MG in 2011 15,16 which stated that the fundamental concern about privacy is usually also the main concern of the participants when they are deciding whether to donate their samples to Biobanks. Their study showed that up to 90% of people were concerned about their privacy Thus, concluded that consequences of breaking privacy could substantially affect public's willingness to participate and substantially delay the research.…”
Section: Discussionsupporting
confidence: 85%
“…i.e, limiting to oneself and not disclosing to others. [10][11][12][13][14] These findings were in agreement with the study done by Kaufman DJ 2009 and Hansson MG in 2011 15,16 which stated that the fundamental concern about privacy is usually also the main concern of the participants when they are deciding whether to donate their samples to Biobanks. Their study showed that up to 90% of people were concerned about their privacy Thus, concluded that consequences of breaking privacy could substantially affect public's willingness to participate and substantially delay the research.…”
Section: Discussionsupporting
confidence: 85%
“…This supports previous studies of informed consent understanding for adults consenting to participate in research studies. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, our study is the first to measure actual and perceived understanding of informed consent for parents who gave permission for their children to participate in a biobanking study. More than half of the parents were uncertain or responded incorrectly to the main questions of the study, including those regarding the use and storage of samples and the handling of results from the study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Others also found participants to express a strong desire to be informed about research results. 14,[16][17][18] Once recruited by biobanks, participants will not always want the information they initially desired. Therefore, taking into account that participants may change their minds during the course of the study, assessing information preferences is an ongoing process.…”
Section: Discussionmentioning
confidence: 99%